2017
DOI: 10.1136/sextrans-2016-053071
|View full text |Cite
|
Sign up to set email alerts
|

Advancing prevention of sexually transmitted infections through point-of-care testing: target product profiles and landscape analysis

Abstract: Objectives Advancing the field of point-of-care testing (POCT) for STIs can rapidly and substantially improve STI control and prevention by providing targeted, essential STI services (case detection and screening). POCT enables definitive diagnosis and appropriate treatment in a single visit and home and community-based testing. results The landscape analysis identified diagnostic tests that are either available on the market, to be released in the near future or in the pipeline. The TPPs specify 28 analytical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 36 publications
1
59
1
Order By: Relevance
“…In the tHDA limit of detection studies, there is a slight reduction in the device detection limit compared to in-tube experiments, however, both methods were able to detect as few as 10 copies of DNA in a subset of reactions. Further development of this platform will focus on reducing the turnaround time from 80 min to less than 60 min and decreasing the required user interaction to fewer than three steps in order to align it with the recently published target produce profile for point-of-care NG diagnostic tests (Toskin et al 2017). Presently, patient sample processing and reaction chamber drying require 30 min, amplification requires 45 min, and LFS interpretation another 5 min.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the tHDA limit of detection studies, there is a slight reduction in the device detection limit compared to in-tube experiments, however, both methods were able to detect as few as 10 copies of DNA in a subset of reactions. Further development of this platform will focus on reducing the turnaround time from 80 min to less than 60 min and decreasing the required user interaction to fewer than three steps in order to align it with the recently published target produce profile for point-of-care NG diagnostic tests (Toskin et al 2017). Presently, patient sample processing and reaction chamber drying require 30 min, amplification requires 45 min, and LFS interpretation another 5 min.…”
Section: Discussionmentioning
confidence: 99%
“…Food and Drug Administration 2011). A more recent target product profile developed by international STI experts indicated that 90% sensitivity and 90% specificity would be acceptable for surveillance and screening in a test that required less than 60 min (Toskin et al 2017). A limitation to our pilot study is that the sample size is underpowered to determine true diagnostic sensitivity and specificity of the paperfluidic device.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors, agree that the device characteristics that are beneficial are following the WHO guidelines for PoC diagnostics, which are symbolized by the acronym, ASSURED; which stands for Affordable, Sensitive, Specific, User-friendly, Rapid and robust, Equipment-free and Delivered to those who need them. These requirements are regularly mentioned in publications [ 20 , 22 , 45 , 46 , 47 , 48 ], but it also has to be noted that these are ideal and strong requirements that only a selected few devices can meet [ 21 ].…”
Section: Researchmentioning
confidence: 99%
“…Recent publications have called for the advancement of point-of-care testing (POCT) for STIs, as they promise significantly improved performance compared with syndromic management. POCT potentially avoids overuse and misuse of antimicrobials and could thus decrease the selection of antimicrobial resistance (AMR) in STI pathogens and bystander commensal or pathogenic bacterial species, lower testing costs for patients and healthcare systems, reduce waiting times, speed up and increase accurate treatment, and improve patient follow-up 8–11. Accurate, rapid and affordable POCT could increase access to testing and identification of STIs in a single-patient visit in both LMICs and high-income countries (HICs) and could be used at all levels of the healthcare system while also contributing to the improvement of STI surveillance through POCT connectivity 12…”
Section: Introductionmentioning
confidence: 99%